Ethnomathematics: Exploration of Fractal Geometry in Gate Ornaments of the Sumenep Jamik Mosque Using the Lindenmayer System - Alghar, Muhammad Zia; Marhayati, Marhayati (Indonesian Journal of Science and Mathematics Education, 2023)
Jamik Sumenep Mosque, a heritage site of the Sumenep Kingdom, was built to emphasize the acculturation of Chinese, Islamic, and Madurese cultures. This ethnomathematics research aims to reveal and explore the fractal geometry forms in the gateway of Jamik Sumenep Mosque. This study employed qualitative methods with an ethnographic approach. Research data were gathered through observation, field notes, documentation, interviews, and literature studies. Field observations were computationally analyzed using the Lindenmayer system through the L-Studio application to examine fractal shapes. The study found that the length and angle size of the ornamental parts form the basis of fractal geometry in the mosque gateway's ornamentation, thereby confirming the presence of fractal geometry concepts. These findings can be utilized in teaching fractal geometry, applied mathematics, and computational geometry. Further research could explore non-Euclidean geometry methods, such as stochastic L-system methods.